THE ROLE OF LEGAL AID SERVICES IN FACILITATING ACCESS TO JUSTICE FOR MARGINALIZED INDIVIDUALS IN HINDU DIVORCE CASES - Manjit Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper examines the critical role played by legal aid services in enabling marginalized individuals to access justice within the context of Hindu divorce cases. This research explores the particular difficulties marginalized people encounter while navigating these complex legal procedures, drawing on the unique cultural and legal context of Hindu marriage and divorce proceedings. The research reviews the value of legal aid services in balancing equality for marginalized people through an investigation of the barriers to accessing justice, such as financial limitations, cultural norms, and institutional disparities. Legal aid programs enable underprivileged persons to express their rights and achieve equitable outcomes by offering customized legal counsel, guidance, and assistance for Hindu divorce cases. The study also looks at successful methods for legal aid provision in Hindu divorce proceedings, emphasizing how these models enhance access to justice and encourage equal outcomes. The paper recommends these steps as a means of promoting a more accessible and inclusive judicial system that attends to the interests of underrepresented parties in Hindu divorce processes.